Giant sialolith of submandibular gland: A case report - Dhok, Avinash Parshuram; Bhende, Vikrant Vishnuji; Lahoti, Amol Madanlal (Indian Journal of Case Reports, 2018)
Sialolithiasis is the most common disease of the salivary glands after mumps. The main site of salivary gland stones formation is the submandibular gland, followed by parotid and sublingual gland. Here, we report the case of a 70-year-old male with giant submandibular gland calculus of size 3.3 cm × 2.1 cm × 1.5 cm with an inflamed gland. We reviewed the literature and found that submandibular gland sialolith measuring 10 mm in greatest dimension is very common, but large sialolith like the one seen in this case is relatively rare and only 18 cases have been reported in the literature with calculus size >3.0 cm till date. The largest reported sialolith was 6 cm in length and had a weight of 50 g. Non-enhanced computed tomography is recommended when salivary stones are suspected.